Mechanism of interaction of pressure waves at a discrete partial blockage. (April 2016) - Meniconi, Silvia; Brunone, Bruno; Ferrante, Marco; Capponi, Caterina
Abstract: This paper analyses the mechanism of interaction between an incident pressure wave and blockages of different geometrical characteristics (i.e., a butterfly and a ball valves, two short stretches of pipe with a reduced diameter, and a device simulating a longitudinal body blockage) by means of laboratory and numerical tests. Experiments have shown that the mechanism of interaction with pressure waves is influenced by their path through the device: sinuous because of the device body for partially closed in-line valves (type I mechanism), and straight for the small bore pipe devices (type II mechanism). Type I mechanism is characterized by a rise followed by an almost constant value whereas in type II one a drop occurs after the rise. To complete the investigation the effect of the pre-transient condition is discussed. Abstract : Highlights: We examined the transient response of discrete partial blockages of different geometrical characteristics. Laboratory and numerical experiments concerned both valves and small bore pipe devices simulating a partial blockage. Experiments pointed out that two mechanisms of interaction between pressure waves and partial blockages can occur. The mechanism of interaction depends on the path of pressure waves through the partial blockage. The effect of the pre-transient conditions was examined.